Governance and Public Service Delivery in India - Farzana Afridi (Institute of Labor Economics (IZA), 2017)
Citizens in low income democracies depend, to a large extent, on the state for the provision of basic services either due to absence of a market for these services or poverty. This paper synthesizes the findings of the International Growth Centre (IGC) supported research on governance and public service delivery in India. Existing research suggests that the quality of public services affects economic growth via its impact on poverty alleviation, human capital formation and corruption. There is near consensus, however, that India has had limited success in reducing poverty and enhancing human capital inspite of myriad programs that provide free or heavily subsidised essential services to its citizens. The paper identifies incentives, transparency and state capacity as the key challenges to reducing the governance deficit in India. IGC supported research emphasizes building state capacity to implement and monitor public programs, rewarding performance of civil servants and providing information to stakeholders as key policies that can be implemented, and scaled up, to both improve the quality of public service delivery and spur economic growth.
Keywords: H11; H41; H53; O43; 330; governance; public services; incentives; transparency; capacity; India